A dictionary of earth sciences - Allaby, Michael (Oxford ; New York : Oxford University Press, 2008)
Contains over six thousand alphabetically arranged entries that provide definitions of words related to the Earth sciences, covering climatology, economic geology, geochemistry, oceanography, paleontology, petrology, and volcanology.
Cover title: Oxford dictionary of earth sciences.
Includes bibliographical references (p. [647]-654).
Choice
Choice, November 2008
Library Journal
Library Journal, August 2008
Keywords: Earth sciences -- Dictionaries